1, 25 Dihydroxyvitamin D3 Enhances the Antifibroid Effects of Ulipristal Acetate in Human Uterine Fibroids. (June 2019) - Ali, Mohamed; Shahin, Sara Mahmoud; Sabri, Nagwa Ali; Al-Hendy, Ayman; Yang, Qiwei
Background: Both European and American trials showed superior effect of ulipristal acetate (UPA) to placebo. However, the latter, which included black patients with known higher vitaminD3 deficiency risk, showed lower rate of amenorrhea responders and insignificant uterine fibroid (UF) size reduction. Our objective is to investigate whether adding vitamin D3 to UPA can enhance UPA potency on UF phenotype in vitro. Methods: We screened the antiproliferative effect of different (UPA/vitaminD3) combinations on UF cell proliferation using dimethylthiazolyl diphenyltetrazolium bromide assay. Cells then were treated with UPA 100 nM in the presence or absence of vitamin D3 100 nM, and expression level of several markers related to proliferation, apoptosis, fibrosis, inflammation, and angiogenesis was measured on RNA or at protein level using quantitative real-time polymerase chain reaction, Western blot, immunofluorescence, or multiplex enzyme-linked immunosorbent assay techniques. Results: Significant dose- and time-dependent growth inhibitory effects of UPA/vitamin D3 combinations were observed compared to untreated cells at 2 and 4 days ( P < .05). Importantly, vitamin D3 /UPA combination significantly reduced cell proliferation as compared to UPA at 2, 4, 6, and 8 days ( P < .05). Combination treatment significantly decreased protein expression of proliferation markers Ki-67, PCNA, and CyclinD1 by more than 50% compared to UPA ( P < .05) along with a significant increase in apoptosis induction. Combination treatment resulted in a 2-fold decrease in protein levels of extracellular matrix markers collagen-1 and fibronectin besides pro-fibrogenic cytokine transforming growth factor β3 ( P < .05). Moreover, it significantly decreased the production of pro-inflammatory cytokines interleukins 6, 8, 1α, and 1β compared to UPA ( P < .05). Conclusion: Combination of vitamin D3 with UPA exhibits additional and orchestrated anti-UF effects, therefore might offer a more favorable clinical option.